Examining Student Writing Proficiencies Across Genres: Results of an Intervention Study. (2nd July 2016) - Dostal, Hannah M.; Wolbers, Kimberly A.
Abstract: This study examines the patterns of growth across both taught and untaught genres of writing for deaf and hard of hearing students in grades 4–6. Twenty-three students were exposed to Strategic and Interactive Writing Instruction (SIWI) for 5 weeks, during which time they received guided, interactive instruction focused on how writers address particular purposes and audiences with their writing. By examining student writing samples before and after both regular writing instruction and SIWI using genre-specific rubrics, we investigated whether students transfer and generalize writing strategies and processes learned in one genre to writing in a genre for which they did not receive instruction, in this case: information report writing. We found that after 5 weeks focused on recount genre instruction, students spontaneously transfer competencies related to genre-specific features that were not explicitly taught, and that students with greater language proficiency did so more effectively. We discuss these findings as they relate to theories of composition and language competence, and generate implications for writing instruction that can lead to growth in writing.